(untitled) (Research, Society and Development, 2022)
Located in the state of Paraíba, the Epitácio Pessoa reservoir represents one of the main springs in the northeast, responsible for supplying the important city of Campina Grande, and other neighboring cities. The reservoir reached the lowest volumetric level017 of its innovations in March, when it reached about 3% of its total water storage capacity, it has the possibility of replenishing without water supply in cities that depend on its water availability. During the imminent threat, still in March 2017, the dam started in the waters of the São Francisco River Transposition, which came to change the chaotic scenario that is found in the reserve. Therefore, the present work aimed to analyze the volumetric behavior of the Epitácio Pessoa weir between January 2012 and June 2022 through the study of the time series of the weir available on the AESA website. Using the R 4.1.2 software, through the ’autoarima’ function of the ’forecast’ package, it was possible to verify that the ARIMA model (therefore better accuracy) was chosen to describe the series of behavior. the volumetric behavior expected for the following months (July to December 2022).